Expectations on old age in the opinion of young people with regard to sociodemographic factors - Ewa Smoleń; Weronika Kolbuch; Paulina Poznańska; Karolina Sobota; Justyna Stawarczyk; Wioletta Boroń; Estera Jursa (Kazimierz Wielki University, 2017)
Introduction. Old age is a natural, individual and inherent part of life, conditioned by numerous factors. Its advent is often surprising, so it is worth to prepare for it. Poland is one of the aging countries, where the proportion of older people is increasing and life expectancy is on the rise. Aim. Determining the expectations of youth in relation to old age in terms of sociodemographic factors. Materials and methods. The study was conducted in 2016 in Sanok among 360 respondents (120 students and 120 gymnasium students and 120 high school students). Diagnostic survey and survey technique were used. The research tool was the author's questionnaire survey. Statistical tests used were: the V Kramer, Chi-square and Phi tests. The significance level of p <0.05 was assumed. Results. More than half of the youth surveyed thought of their old age. A significant percentage declared that they were afraid of old age and the fear was more often expressed by women. Young people in their old age are most afraid of diseases. Main expectations regarding old age in the opinion of young people are the maintenance of health and the ability to fulfill dreams. A significant percentage of respondents indicated that in the old age they would have an excess of free time. Only about one-third of young people indicated that they had been preparing for retirement all their lives. Half of the respondents declared that when they would get older they would like te continue education. Conclusions. A conscious entry into the old age stage favors the acceptance of inevitable changes and adaptations to this period of life. This process should begin at the stage of lifelong learning.